Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpsyt.2022.805380
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Spiritual Well-Being of Patients With Esophageal Cancer Aged Over 50 Years: The Mediating Role of Rumination

Abstract: BackgroundSpiritual well-being plays an important role in helping patients cope with disease. Previous studies have investigated the association between social support and spiritual well-being, whereas few studies have explored the relationship in patients with esophageal cancer (EC), and the mechanisms behind this pathway have not been thoroughly examined.ObjectiveThis study aimed to explore the relationship between social support and spiritual well-being of Chinese patients with EC aged over 50 years and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Twenty‐six studies were quantitative designs and were conducted in mainland China ( n = 18), Taiwan ( n = 6), and the USA ( n = 2). Among them, five studies explored spiritual needs (Cheng et al, 2018; Deng et al, 2015; Du et al, 2022), spiritual state (Cheng et al, 2019), and spiritual nursing needs (Li et al, 2017); 11 studies examined the correlation between spiritual aspects and other variables (Chang et al, 2022; Cho & Lu, 2017; Feng et al, 2021; Guo et al, 2022; Kao et al, 2013; Li et al, 2012, 2022; Tao et al, 2022; Wang & Lin, 2016; Yang et al, 2021; Yeung et al, 2014); seven studies were conducted to translate spirituality‐related instruments originally developed in Western countries into Chinese for use with Chinese people with cancer (Astrow et al, 2012; Lin et al, 2015; Liu et al, 2016; Lo et al, 2016; Tang & Kao, 2017; Xie et al, 2019; Zhao et al, 2019); and three studies aimed to examine the effects of interventions on the spirituality of Chinese people with cancer (Chen et al, 2021; Sun et al, 2021; Xiao et al, 2022). One study with a mixed methods design was conducted in mainland China to explore the quality of life (including a spiritual dimension) of breast cancer survivors (Cheng et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐six studies were quantitative designs and were conducted in mainland China ( n = 18), Taiwan ( n = 6), and the USA ( n = 2). Among them, five studies explored spiritual needs (Cheng et al, 2018; Deng et al, 2015; Du et al, 2022), spiritual state (Cheng et al, 2019), and spiritual nursing needs (Li et al, 2017); 11 studies examined the correlation between spiritual aspects and other variables (Chang et al, 2022; Cho & Lu, 2017; Feng et al, 2021; Guo et al, 2022; Kao et al, 2013; Li et al, 2012, 2022; Tao et al, 2022; Wang & Lin, 2016; Yang et al, 2021; Yeung et al, 2014); seven studies were conducted to translate spirituality‐related instruments originally developed in Western countries into Chinese for use with Chinese people with cancer (Astrow et al, 2012; Lin et al, 2015; Liu et al, 2016; Lo et al, 2016; Tang & Kao, 2017; Xie et al, 2019; Zhao et al, 2019); and three studies aimed to examine the effects of interventions on the spirituality of Chinese people with cancer (Chen et al, 2021; Sun et al, 2021; Xiao et al, 2022). One study with a mixed methods design was conducted in mainland China to explore the quality of life (including a spiritual dimension) of breast cancer survivors (Cheng et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…spiritual transcendence such as selfless social responsibility in Confucianism) was added (Lo et al, 2016), specific examples such as ‘Chinese god’, ‘Buddha’, ‘bodhisattva’ and ‘ancestor’ were added (Cheng et al, 2018; Du et al, 2022; Zhao et al, 2019), and the term was paraphrased as ‘heaven or deities’ (Tao et al, 2022). For religious activities, some religious terms were replaced with culturally appropriate concepts such as from ‘scripture reading’ to ‘positive reading’ (Cheng et al, 2018; Du et al, 2022; Guo et al, 2022; Li et al, 2017; Xie et al, 2019), ‘prayer’ was supplemented with terms ‘chanting’, ‘worshipping deities’, ‘burning incense’ and ‘offering tribute’ (Tao et al, 2022), specific examples such as ‘chanting scriptures’, ‘praying’, ‘morning ceremony’ were added (Guo et al, 2022; Li et al, 2022; Xie et al, 2019), and ‘sacrament’, ‘mass’, and other rituals not commonly performed by Chinese people were removed (Cheng et al, 2018; Du et al, 2022). As for the term ‘spirituality’, which is unfamiliar to many Chinese, the phrase ‘writing about my spirituality’ was modified to ‘writing down the spiritual world in my brain’, and specific examples of spiritual resources such as ‘temple’, ‘church’ or ‘other religious sites’ were added (Guo et al, 2022; Li et al, 2017; Xie et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other studies have shown that depression is negatively correlated with deliberate rumination ( 18 ). A study of Chinese patients over 50 years old with esophageal cancer explored the relationship between social support and mental wellbeing, finding that they were negatively correlated with intrusive rumination and positively correlated with deliberate rumination ( 19 ). In addition, a study suggests that continuous deliberate rumination is a protective factor against post-traumatic stress disorder and a predictor of post-traumatic growth ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rumination was found to be linked to social support and the severity of traumatic situations (Stockton et al, 2011;Tedeschi & Calhoun, 2004). Coping strategies such as positive coping and emotional expression can influence rumination (Pan et al, 2022;Wang et al, 2023). Therefore, it is necessary to identify predictors of rumination trajectory classes in young and middle-aged stroke survivors.…”
Section: Introductionmentioning
confidence: 99%